The Effectiveness of the Socialization of Regional Regulation Number 1 of 2024 on Waste Retribution in Gunung Pangilun Subdistrict, Padang City - Elfemi, Nilda; Febriani, Atika; Syafrinandes, Arpes; Siputra, Bimo; Nasution, Randi; Diani, Rosi Putri; Putri, Zelwa Misdagita (Universitas PGRI Sumatera Barat, 2025)
This study evaluates the effectiveness of the socialization of Regional Regulation (Perda) Number 1 of 2024 concerning Waste Retribution in Gunung Pangilun Subdistrict, Padang City. The research employed a qualitative approach with data collection techniques including interviews, observations, and document analysis. The findings indicate that the socialization has improved public understanding; however, resistance to retribution fees and the lack of involvement of community leaders remain issues. The study recommends more inclusive communication strategies and the active engagement of community figures to enhance public acceptance and compliance with this policy.